Effects of Nutrition Training on People's Diet and Nutritional Status: An Intervention Study - Miksusanti Miksusanti; Ismed Ismed; Yani Maidelwita; Muntasir Muntasir; Sulistyo Andarmoyo (Journal of World Future Medicine, Health and Nursing, 2024)
An unbalanced diet can have a negative impact on people's nutritional status. Therefore, nutrition training is considered an effective intervention strategy to improve diet and nutritional status. This research aims to evaluate the effect of nutrition training on people's eating patterns and nutritional status through an intervention study. This research method uses an intervention approach with a pre-test and post-test design involving people randomly selected from a certain area. Nutrition training is held with a focus on understanding balanced nutrition and implementing healthy eating patterns. Dietary pattern data was collected through questionnaires, and nutritional status analysis was carried out by measuring nutritional and anthropometric parameters before and after the intervention. The research results showed a significant increase in people's understanding of balanced nutrition and positive changes in their eating patterns after attending nutrition training. Apart from that, there have been substantial improvements in people's nutritional status, such as increasing body mass index (BMI) and optimal nutritional levels. This research concludes that nutrition training is effective in improving healthy eating patterns and the nutritional status of the community. This shows the importance of a focused intervention approach to increase nutritional awareness and behaviour in an effort to improve overall community health. This research makes an important contribution to the development of nutritional intervention strategies that can be widely applied to enhance community welfare. Therefore, it is recommended to pursue further research with a focus on the long-term effects of nutrition training and increasing accessibility to nutrition resources.